Photocatalytic degradation composite material as well as preparation method and application thereof

By constructing Bi-Bi2WO6 heterojunction and introducing oxygen vacancy, the problems of low photo quantum utilization and unsatisfactory photocatalytic activity of Bi2WO6 photocatalytic materials are solved, and the piezoelectric photocatalytic performance of the material and the degradation efficiency of 2,4-dichlorophenol are significantly improved.

CN119838592AActive Publication Date: 2025-04-18GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510085817.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Due to its wide band gap and limited visible light response range, existing Bi2WO6 photocatalytic materials have low photo quantum utilization and unsatisfactory photocatalytic activity, making it difficult to effectively degrade organic pollutants such as 2,4-dichlorophenol.

Method used

Bi-Bi2WO6 heterojunction of Bi2WO6 nanosheets wrapped in Bi nanometer microspheres was constructed by solvothermal method, and oxygen vacancies were introduced into their lattice structure to optimize the surface structure and energy band structure and enhance photocatalytic activity.

Benefits of technology

The piezoelectric photocatalytic performance of photocatalytic degradation composite materials is significantly improved, the separation efficiency of photogenerated carriers and the absorption capacity of the material to visible light are improved, and the degradation efficiency of 2,4-dichlorophenol is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838592A_ABST
    Figure CN119838592A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of piezoelectric photocatalytic materials, and particularly relates to a photocatalytic degradation composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving bismuth salt and tungstate in a solvent, then adding a reducing agent, and carrying out solvothermal reaction, so that Bi2WO6 is reduced into a Bi simple substance by the reducing agent, a Bi-Bi2WO6 heterojunction of Bi nano microspheres wrapped by Bi2WO6 nanosheets is formed, and a Bi (at) Bi2WO6 material is obtained; the Bi (at) Bi2WO6 material is soaked in a chemical etching agent, so that the Bi (at) Bi2WO6 material is etched by the chemical etching agent to form an oxygen vacancy defect, and the photocatalytic degradation composite material is obtained. The photocatalytic degradation composite material prepared by the invention has abundant oxygen defects, can significantly increase active sites on the surface of the material and improve piezoelectric photocatalytic performance of the material, and has a significant degradation rate on 2, 4-dichlorophenol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric photocatalytic materials, and in particular relates to a photocatalytic degradation composite material and a preparation method and application thereof. Background Art

[0002] In terms of environmental pollution control, 2,4-dichlorophenol is a common organic pollutant. Due to its high toxicity and difficulty in degradation, it poses a serious threat to the environment and human health. Among the existing degradation methods, piezoelectric photocatalysis technology has attracted much attention due to its high efficiency and environmental protection. Introducing piezoelectric polarization into photocatalysis can enhance the separation ability of photogenerated electron-hole pairs and form piezoelectric photocatalytic materials. Therefore, finding a material with high-voltage electrophotocatalytic activity is still a research hotspot.

[0003] Bi2WO6 has high ferroelectricity and excellent photocatalytic performance, with a ferroelectric constant Pr of 50μC / cm 2 , bandgap width E g The band gap of Bi2WO6 is 2.76eV, showing good application potential in the degradation of organic pollutants and decomposition of water to produce hydrogen. However, due to its wide band gap, it causes a high recombination efficiency of photogenerated carriers, resulting in low photon utilization, and thus the photocatalytic activity is not ideal. At the same time, Bi2WO6 has a limited response range to visible light, which further restricts its practical application under sunlight.

[0004] The existing technology modifies Bi2WO6 by doping, heterostructure construction and surface modification, which improves its photocatalytic performance to a certain extent. However, the preparation method of the existing technology is too complicated, the raw materials are not easy to obtain, and the prepared composite photocatalytic material has low carrier separation efficiency and poor stability, making it difficult to achieve efficient and stable photocatalytic effects. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a photocatalytic degradation composite material and its preparation method and application. The present invention is prepared using safe and readily available raw materials, and the preparation method is simple. The present invention constructs a metal-semiconductor heterojunction by a solvothermal method; then oxygen vacancies are introduced into the lattice structure of the metal-semiconductor heterojunction by a chemical etching reaction, and the catalytic activity of the material is enhanced by optimizing the surface structure of the metal-semiconductor heterojunction. The introduction of oxygen vacancies optimizes the energy band structure of the material, promotes the separation of photogenerated carriers, enhances the light absorption capacity, and provides more active sites for the photocatalytic reaction, thereby greatly improving the piezoelectric photocatalytic performance; the piezoelectric photocatalytic material can induce the generation of a polarization electric field under the action of an external force field to improve the separation of photogenerated electron-hole pairs, so as to significantly improve the photocatalytic performance.

[0006] The present invention dissolves bismuth salt and tungstate in a solvent to obtain a precursor solution, adds a reducing agent to the precursor solution, and reduces Bi2WO6 in the precursor solution to Bi element through a solvothermal reaction, thereby forming a Bi-Bi2WO6 heterojunction in which Bi2WO6 nanosheets wrap Bi nano-microspheres, and obtains a Bi@Bi2WO6 material; the Bi@Bi2WO6 material is immersed in an acid reagent or an alkaline reagent, and under acidic conditions, hydrogen ions react with oxygen atoms of Bi2WO6 in the Bi@Bi2WO6 material to destroy the Bi-O bond structure, so that the oxygen atoms are separated from the Bi2WO6 lattice, thereby forming oxygen vacancies; under alkaline conditions, hydroxide ions coordinate with Bi or W atoms on the surface of the Bi@Bi2WO6 material, thereby changing the surface chemical environment, promoting local reorganization of the lattice and introducing oxygen vacancy defects, and obtaining a photocatalytic degradation composite material. These structural defects significantly increase the active sites on the surface of Bi@Bi2WO6 materials, and at the same time act as capture centers for electron-hole pairs, effectively promoting the separation of photogenerated carriers, thereby significantly improving the piezoelectric photocatalytic performance of the photocatalytic degradation composite material.

[0007] The first object of the present invention is to provide a method for preparing a photocatalytic degradation composite material, comprising the following steps:

[0008] Step 1: dissolving bismuth salt and tungstate in a solvent to obtain a precursor solution, adding a reducing agent to the precursor solution, and reducing Bi2WO6 in the precursor solution into Bi element through a solvothermal reaction to form a Bi-Bi2WO6 heterojunction in which Bi2WO6 nanosheets wrap Bi nanospheres, thereby obtaining a Bi@Bi2WO6 material.

[0009] It should be noted that the reaction temperature is the main condition in the solvent thermal reaction process of the Bi@Bi2WO6 material prepared by the present invention. The reaction temperature directly affects the Bi by regulating the activity and reaction kinetics of the reducing agent. 3+ Therefore, by exploring the effect of solvothermal reaction temperature on the formation and growth of Bi2WO6 nanosheets, the present invention found that the reaction temperature plays a key role in the formation and growth of Bi nanospheres. When the temperature is lower than 220°C, the Bi in Bi2WO6 is reduced due to insufficient reaction kinetics. 3+ The reduction rate is slow, and Bi in Bi2WO6 cannot be fully reduced to generate nano-microspheres. When the temperature is higher than 280℃, the reduction reaction rate is significantly accelerated, making Bi 3+ Completely reduced to Bi element. The preferred solvent thermal reaction temperature of the present invention is 220°C to 280°C, and the preferred solvent thermal reaction time is 12h to 24h.

[0010] Preferably, the reducing agent is hexadecyltrimethylammonium bromide.

[0011] The specific preparation process of the Bi@Bi2WO6 material of the present invention is: dissolving bismuth salt and tungstate in a solvent to obtain a precursor solution; adding a reducing agent to the precursor solution under stirring conditions, and using a 2 mol / L alkaline solution to adjust the pH of the solution to neutral to obtain a suspension; transferring the suspension to a reactor to perform a solvent thermal reaction, cooling to room temperature after the reaction is completed, washing, centrifuging and drying to obtain the Bi@Bi2WO6 material.

[0012] It should also be noted that since the pH value of the precursor solution is 1-2, the present invention explores the effect of pH gradient on Bi element and Bi2WO6 nanosheets, and finds that changes in pH value will affect the growth of crystals, and acidic or alkaline conditions will inhibit the formation of Bi2WO6 nanosheets; in addition, the performance of Bi@Bi2WO6 materials synthesized under acidic or alkaline conditions is worse than that of Bi@Bi2WO6 materials under neutral conditions. Therefore, the present invention adjusts the precursor solution by adding an alkaline solution, and selects neutral for subsequent research. Preferably, the alkaline solution is one of sodium hydroxide, potassium hydroxide and ammonia.

[0013] The molar ratio of the bismuth salt, tungstate and reducing agent is 1-2:0.5-1:0.27-0.55.

[0014] Preferably, the bismuth salt is one of bismuth nitrate pentahydrate and bismuth chloride.

[0015] Preferably, the tungstate is one of sodium tungstate and ammonium tungstate.

[0016] Preferably, the solvent is one of ethylene glycol and ethanol.

[0017] Step 2: Immerse the Bi@Bi2WO6 material in a chemical etchant, so that the chemical etchant etches the Bi@Bi2WO6 material to form oxygen vacancy defects, thereby obtaining a photocatalytic degradation composite material.

[0018] It should be noted that the present invention immerses the Bi@Bi2WO6 material in a chemical etchant, which is an acid or a base. When the chemical etchant is an acid, under acidic conditions, hydrogen ions react with the oxygen atoms of Bi2WO6 in the Bi@Bi2WO6 material, destroying the Bi-O bond structure, so that the oxygen atoms of Bi2WO6 are separated from the lattice, thereby forming oxygen vacancies. In addition, since the generated metallic bismuth has a high chemical reactivity, once the Bi element is exposed to an acidic environment, partial controllable dissolution will occur, thereby forming a rough porous structure and nanoscale holes on the surface of the material. When the chemical etchant is an alkali, under alkaline conditions, hydroxide ions react with Bi or W atoms on the surface of the Bi@Bi2WO6 material to change the surface chemical environment, promote partial reorganization of the crystal lattice of the Bi@Bi2WO6 material, and introduce oxygen vacancy defects. These structural defects can significantly increase the active sites on the surface of the Bi@Bi2WO6 material, which can serve as the capture center of electron-hole pairs, promote the separation of photogenerated carriers, and thus improve the photocatalytic performance of the material.

[0019] Preferably, the usage ratio of the Bi@Bi2WO6 material and the chemical etchant is 50mg-100mg:100mL.

[0020] Preferably, the concentration of the chemical etchant is 0.05 mol / L to 0.3 mol / L.

[0021] Preferably, the soaking time is 30 min to 240 min.

[0022] Preferably, the acid is one of hydrochloric acid, nitric acid and phosphoric acid; and the alkali is one of sodium hydroxide, potassium hydroxide and ammonium hydroxide.

[0023] The second object of the present invention is to provide a photocatalytic degradation composite material prepared by the above preparation method.

[0024] The third object of the present invention is to provide the use of the above-mentioned photocatalytic degradation composite material in the degradation of 2,4-dichlorophenol.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention constructs a Bi-Bi2WO6 heterojunction in which Bi2WO6 nanosheets encapsulate Bi single-substance nano-microspheres through a solvothermal reaction; and then introduces oxygen vacancies into the lattice structure of the Bi-Bi2WO6 heterojunction through a chemical etching reaction. When chemical etching is performed under acidic conditions, hydrogen ions react with oxygen atoms of Bi2WO6 in the Bi@Bi2WO6 material, destroying the Bi-O bond structure, causing oxygen atoms to detach from the Bi2WO6 lattice, thereby forming oxygen vacancies; when chemical etching is performed under alkaline conditions, hydroxide ions react with Bi or W atoms on the surface of the Bi@Bi2WO6 material to change the surface chemical environment, promote partial reorganization of the lattice, and introduce oxygen vacancy defects. These structural defects significantly increase the active sites on the surface of Bi@Bi2WO6 materials, and at the same time, they act as the capture center of electron-hole pairs, effectively promoting the separation of photogenerated carriers; secondly, they adjust the energy band structure of Bi@Bi2WO6 materials, reduce the recombination rate of photogenerated electrons and holes, and enhance the material's absorption capacity for visible light, thereby significantly improving the piezoelectric photocatalytic performance of the photocatalytic degradation composite material. Under the action of piezoelectric polarization, the migration of photogenerated electron-hole pairs to the surface of the material can be accelerated, thereby continuously enhancing the catalytic degradation process of 2,4-dichlorophenol.

[0027] The present invention adopts a simple solvent thermal method to synthesize a Bi@Bi2WO6 heterojunction, and then combines a chemical etching method to immerse the Bi@Bi2WO6 material in a chemical etchant, so that the chemical etchant etches the Bi@Bi2WO6 material to form oxygen vacancy defects, thereby obtaining a photocatalytic degradation composite material; the preparation process is simple, green and pollution-free, adopts a solvent thermal method combined with chemical etching for preparation, is easy to operate, and the raw materials are cheap and easily available, and are suitable for large-scale production.

[0028] The present invention can accurately control the oxygen defect concentration on the surface of the photocatalytic degradation composite material through chemical etching, so that it has more abundant active sites and effectively enhances the activity of the photocatalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD characterization diagrams of the photocatalytic degradation composite materials prepared in Examples 1 to 3 of the present invention and the Bi@Bi2WO6 material prepared in Comparative Example 7.

[0030] Figure 2 XRD characterization diagrams of the photocatalytic degradation composite materials prepared in Examples 5 to 7 of the present invention and the Bi@Bi2WO6 material prepared in Comparative Example 7.

[0031] Figure 3 XRD characterization diagrams of the Bi2WO6 materials prepared in Comparative Examples 1 to 7 of the present invention and the Bi@Bi2WO6 material prepared in Comparative Example 8.

[0032] Figure 4 SEM images of the Bi2WO6 material prepared in Comparative Example 1 of the present invention, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 1 to 8; wherein (a) is Comparative Example 1, (b) is Comparative Example 7, (c) is Example 2, (d) is Example 1, (e) is Example 3, (f) is Example 4, (g) is Example 7, (h) is Example 6, (i) is Example 5, and (j) is Example 8.

[0033] Figure 5 The removal rates of 2,4-DCP by the Bi2WO6 material prepared in Comparative Example 1 of the present invention, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 1 to 3 are shown.

[0034] Figure 6 The removal rates of 2,4-DCP by the Bi2WO6 material prepared in Comparative Example 1 of the present invention, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 5 to 7 are shown.

[0035] Figure 7 These are electron paramagnetic resonance characterization diagrams of the Bi2WO6 material prepared in Comparative Example 1 of the present invention, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 1 and 5. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand that the technical solution of the present invention can be implemented, the present invention is further described below in conjunction with specific embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.

[0038] The invention is further described below through specific examples.

[0039] Example 1

[0040] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0041] Step 1: Preparation of Bi@Bi2WO6 material:

[0042] 1.1) Dissolve 2 mmol of Bi(NO3)3·5H2O and 1 mmol of Na2WO4·2H2O in 60 mL of ethylene glycol to obtain a precursor solution.

[0043] 1.2) Add 0.27 mmol of hexadecyltrimethylammonium bromide to the precursor solution under stirring, and add 2 mol / L of KOH to adjust the pH to 7.00, and stir for 30 min to obtain a suspension.

[0044] 1.3) The suspension was transferred to a 100 mL polytetrafluoroethylene reactor and kept at a constant temperature of 240°C for 24 h. After cooling to room temperature, the precipitate generated by the reaction was thoroughly washed three times with deionized water and anhydrous ethanol, respectively, and dried at 60°C for 24 h. The Bi@Bi2WO6 material was obtained after grinding.

[0045] Step 2: Preparation of photocatalytic degradation composite material:

[0046] 50 mg of Bi@Bi2WO6 material was immersed in 100 mL of a sodium hydroxide solution with a concentration of 0.1 mol / L and stirred for 30 min to perform a chemical etching reaction to obtain a photocatalytic degradation composite material, which was recorded as 0.1_Alk_BBW.

[0047] Example 2

[0048] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0049] The difference between this embodiment and embodiment 1 is:

[0050] In this example, the concentration of the sodium hydroxide solution is 0.05 mol / L; the photocatalytic degradation composite material obtained in this example is recorded as 0.05_Alk_BBW.

[0051] Example 3

[0052] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0053] The difference between this embodiment and embodiment 1 is:

[0054] In this example, the concentration of the sodium hydroxide solution is 0.2 mol / L; the photocatalytic degradation composite material obtained in this example is recorded as 0.2_Alk_BBW.

[0055] Example 4

[0056] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0057] The difference between this embodiment and embodiment 1 is:

[0058] The concentration of the sodium hydroxide solution in this example is 0.3 mol / L; the photocatalytic degradation composite material obtained in this example is recorded as 0.3_Alk_BBW.

[0059] Example 5

[0060] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0061] The difference between this embodiment and embodiment 1 is:

[0062] The chemical etching agent of this embodiment is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.2 mol / L; the photocatalytic degradation composite material obtained in this embodiment is recorded as 0.2_Aci_BBW.

[0063] Example 6

[0064] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0065] The difference between this embodiment and embodiment 1 is:

[0066] The chemical etching agent of this embodiment is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.1 mol / L; the photocatalytic degradation composite material obtained in this embodiment is recorded as 0.1_Aci_BBW.

[0067] Example 7

[0068] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0069] The difference between this embodiment and embodiment 1 is:

[0070] The chemical etching agent of this embodiment is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.05 mol / L; the photocatalytic degradation composite material obtained in this embodiment is recorded as 0.05_Aci_BBW.

[0071] Example 8

[0072] This embodiment provides a method for preparing a photocatalytic degradation composite material.

[0073] The difference between this embodiment and embodiment 1 is:

[0074] The chemical etching reagent of this embodiment is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.3 mol / L; the photocatalytic degradation composite material obtained in this embodiment is recorded as 0.3_Aci_BBW.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing Bi2WO6 material.

[0077] 1.1) Dissolve 2 mmol of Bi(NO3)3·5H2O and 1 mmol of Na2WO4·2H2O in 60 mL of ethylene glycol to obtain a precursor solution.

[0078] 1.2) Add 0.55 mmol of hexadecyltrimethylammonium bromide to the precursor solution under stirring, and add 2 mol / L of KOH to adjust the pH to 7.00, and stir for 30 min to obtain a suspension.

[0079] 1.3) The suspension was transferred to a 100 mL polytetrafluoroethylene reactor and kept at a constant temperature of 180°C for 24 h. After cooling to room temperature, the precipitate generated by the reaction was thoroughly washed three times with deionized water and anhydrous ethanol respectively, dried at 60°C for 24 h, and ground to obtain Bi2WO6 material, which was recorded as BW.

[0080] The difference between this comparative example and Example 1 is:

[0081] In this comparative example, the Bi2WO6 material was not immersed in a chemical etchant to perform a chemical etching reaction.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing Bi2WO6 material.

[0084] The difference between this comparative example and comparative example 1 is:

[0085] The temperature of the solvothermal reaction in this comparative example was 120°C.

[0086] Comparative Example 3

[0087] This comparative example provides a method for preparing Bi2WO6 material.

[0088] The difference between this comparative example and comparative example 1 is:

[0089] The temperature of the solvothermal reaction in this comparative example was 140°C.

[0090] Comparative Example 4

[0091] This comparative example provides a method for preparing Bi2WO6 material.

[0092] The difference between this comparative example and comparative example 1 is:

[0093] The temperature of the solvothermal reaction in this comparative example was 160°C.

[0094] Comparative Example 5

[0095] This comparative example provides a method for preparing Bi2WO6 material.

[0096] The difference between this comparative example and comparative example 1 is:

[0097] The temperature of the solvothermal reaction in this comparative example was 200°C.

[0098] Comparative Example 6

[0099] This comparative example provides a method for preparing Bi2WO6 material.

[0100] The difference between this comparative example and comparative example 1 is:

[0101] The temperature of the solvothermal reaction in this comparative example was 220°C.

[0102] Comparative Example 7

[0103] This comparative example provides a method for preparing Bi@Bi2WO6 material.

[0104] The difference between this comparative example and comparative example 1 is:

[0105] The temperature of the solvent thermal reaction in this comparative example is 240° C., and the Bi@Bi2WO6 material obtained in this comparative example is recorded as BBW.

[0106] Comparative Example 8

[0107] This embodiment provides a method for preparing Bi@Bi2WO6 material.

[0108] The difference between this comparative example and comparative example 1 is:

[0109] The temperature of the solvothermal reaction in this comparative example was 280°C.

[0110] Experimental Section

[0111] 1. Material Characterization

[0112] 1. XRD characterization

[0113] Figure 1 The XRD characterization diagrams of the photocatalytic degradation composite materials prepared in Examples 1 to 3 and the Bi@Bi2WO6 material prepared in Comparative Example 7 are shown. Figure 1 It can be seen that BBW without NaOH etching shows strong Bi2WO6 and Bi diffraction signals. When the concentration of NaOH increases from 0.05M to 0.2M, the diffraction peak intensity of Bi element gradually decreases, while the diffraction peak intensity of Bi2WO6 is significantly enhanced. This shows that the crystal structure of the material has changed significantly during the alkaline etching process, indicating that the present invention causes slight damage to the lattice of the photocatalytic degradation composite material through NaOH etching and introduces oxygen defects.

[0114] Figure 2XRD characterization diagrams of the photocatalytic degradation composite materials prepared in Examples 5 to 7 and the Bi@Bi2WO6 material prepared in Comparative Example 7. The XRD spectrum shows that BBW without HCl etching exhibits strong Bi2WO6 and Bi diffraction signals. After being etched with hydrochloric acid of different concentrations, as the concentration of hydrochloric acid increases, the diffraction peaks of these etched photocatalytic degradation composite materials show that the main crystalline phases are still Bi element and Bi2WO6. Compared with BBW, the diffraction peak intensity of the photocatalytic degradation composite material gradually decreases, indicating that the present invention causes slight damage to the lattice of the photocatalytic degradation composite material through HCl etching, and introduces oxygen defects. In addition, when the hydrochloric acid concentration is greater than 0.1M, the characteristic diffraction peak of BiOCl appears, indicating that the moderate concentration of acid etching triggers a surface chemical reaction and part of the Bi 3+ After ion hydrolysis, BiOCl is generated, which distorts the structure of the material, but the main body of the material is still Bi@Bi2WO6.

[0115] Figure 3 The XRD characterization diagram of Bi@Bi2WO6 materials prepared in Comparative Examples 1 to 8. Figure 3 As shown, as the reaction temperature gradually increases from 120°C to 280°C, the crystal structure of the Bi2WO6 material changes significantly. When the temperature is lower than 220°C, the Bi2WO6 material is mainly composed of the Bi2WO6 crystal phase, and the diffraction peak is consistent with the standard card JCPDS No.79-2381; and when the temperature rises to 240°C and above, the diffraction peak of Bi element begins to appear, indicating that the reducing agent reacts with Bi2WO6 to generate Bi element. As the temperature further rises to 280°C, the diffraction peak signal of Bi2WO6 disappears, and only the diffraction peak of Bi element is observed, indicating that Bi2WO6 has been completely reduced. Therefore, the preferred solvent thermal reaction temperature of the present invention is 220°C to 280°C.

[0116] 2. SEM characterization

[0117] Figure 4 SEM images of the Bi2WO6 material prepared in Comparative Example 1, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 1 to 8; wherein (a) is Comparative Example 1, (b) is Comparative Example 7, (c) is Example 2, (d) is Example 1, (e) is Example 3, (f) is Example 4, (g) is Example 7, (h) is Example 6, (i) is Example 5, and (j) is Example 8. Figure 4 Shows the changes in the material during the etching process. Figure 4 In (a), it is observed that BW is formed by the aggregation of nanosheets into irregular microspheres; Figure 4In (b), it is observed that BBW is composed of nanosheets and microspheres, in which the microspheres are mainly reduced Bi elements, while the main component of the nanosheets is Bi2WO6. Figure 4 (c) to (f) in the figure show the alkaline etching process. It can be observed that the microspheres gradually lose their regular shape. At the same time, petal-like morphology appears in the clustered nanosheet structure. With the increase of NaOH concentration, the number of these petals gradually increases. In the acidic etching process, Figure 4 As shown in (g) to (j) in the figure, as the HCl concentration increases, the microsphere structure in the material is gradually destroyed and its number decreases, while the size of the nanosheets covering the surface of the microspheres becomes smaller and their number increases significantly.

[0118] 3. Degradation test

[0119] The present invention weighs 50 mg of the Bi2WO6 material prepared in Comparative Example 1, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite material prepared in Examples 1 to 3, and disperses them in 100 mL and 10 mg / L 2,4-dichlorophenol solutions, respectively, and stirs them in the dark for 30 minutes to obtain a reaction solution to establish adsorption-desorption equilibrium. 5 mL of the reaction solution is extracted and centrifuged every 10 minutes, and then measured at a wavelength of 284 nm using a UV-visible spectrophotometer. The results are as follows: Figure 5 and Figure 6 As shown, a 300W xenon lamp was used to simulate natural light conditions during the degradation process, and the ultrasonic device had a power of 100W and a frequency of 45kHz.

[0120] Figure 5 The removal rates of 2,4-dichlorophenol by the Bi2WO6 material prepared in Comparative Example 1, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 1 to 3. Figure 5 It can be seen that the BW and BBW materials without etching treatment showed lower degradation efficiency, which were 64.79% and 78.11% respectively. In the alkaline etching system, the degradation efficiency of 0.05_Alk_BBW, 0.1_Alk_BBW and 0.2_Alk_BBW were 90.64%, 95.51% and 87.45% respectively; the removal of 2,4-DCP by alkaline-etched Bi@Bi2WO6 material first increased and then decreased, and reached a maximum of 95.51% when the sodium hydroxide concentration was 0.1 mol / L.

[0121] Figure 6 The removal rates of 2,4-dichlorophenol by the Bi2WO6 material prepared in Comparative Example 1, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite materials prepared in Examples 5 to 7 are shown in FIG. Figure 5It can be seen that in the acid etching system, the degradation efficiencies of 0.05_Aci_BBW, 0.1_Aci_BBW and 0.2_Aci_BBW are 75.32%, 83.65% and 86.067%, respectively; the removal rate of 2,4-dichlorophenol by acid-etched Bi@Bi2WO6 material is positively correlated with the added HCl concentration.

[0122] This indicates that the present invention can significantly improve the removal efficiency of 2,4-dichlorophenol by Bi@Bi2WO6 material through the acid-base etching process.

[0123] 4. Degradation mechanism

[0124] The present invention uses electron paramagnetic resonance to characterize the surface states of BW, BBW, 0.1_Alk_BBW and 0.2_Aci_BBW materials. The results are as follows: Figure 7 As shown. The English name of electron paramagnetic resonance is Electron Paramagnetic Resonance, or EPR in English. In EPR, the g factor, or Lande g factor in Chinese, is an important parameter that describes the response of electrons or other particles with magnetic moments in a sample under an external magnetic field. It reflects the relationship between the magnetism of the particle and the external magnetic field, especially the relationship between its total angular momentum and magnetic moment.

[0125] Figure 7 The electron paramagnetic resonance characterization diagrams of the Bi2WO6 material prepared in Comparative Example 1, the Bi@Bi2WO6 material prepared in Comparative Example 7, and the photocatalytic degradation composite material prepared in Examples 1 and 5. Except for the BW material, significant oxygen vacancy signals can be observed in BBW, 0.1_Alk_BBW and 0.2_Aci_BBW materials at a g factor of 2.004, and the signal shown by 0.1_Alk_BBW is the strongest, followed by 0.2_Aci_BBW. This rule is consistent with the phenomenon that 0.1_Alk_BBW has the highest degradation efficiency in the degradation experiment. On BW, the EPR signal is almost not displayed, while the signal intensity on 0.1_Alk_BBW is significantly higher than that on 0.2_Aci_BBW, and the signal intensity is twice that of the latter. This indicates that the acid-base environment does affect the formation of oxygen vacancies during sample preparation: NaOH may destroy the WO bond, causing a disordered crystal structure and generating more oxygen vacancies on the surface, while HCl preferentially reacts with Bi to generate BiOCl, so the content of oxygen vacancies is low. The increase in oxygen vacancies is beneficial to improving the catalytic activity of the material, because oxygen vacancies can provide more active sites, promote the separation of photogenerated electron-hole pairs, enhance photocatalytic performance, and improve the electronic conductivity and light absorption capacity of the material, thereby improving the efficiency of photocatalytic degradation of pollutants.

[0126] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a photocatalytic degradation composite material, characterized in that: The following steps are involved: Dissolving bismuth salt and tungstate in a solvent to obtain a precursor solution; adding a reducing agent to the precursor solution, and reducing Bi2WO6 in the precursor solution to Bi element through a solvothermal reaction to form a Bi-Bi2WO6 heterojunction in which Bi2WO6 nanosheets wrap Bi nanospheres, thereby obtaining a Bi@Bi2WO6 material; The Bi@Bi2WO6 material is immersed in a chemical etchant, so that the chemical etchant etches the Bi@Bi2WO6 material to form oxygen vacancy defects, thereby obtaining a photocatalytic degradation composite material.

2. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The usage ratio of the Bi@Bi2WO6 material and the chemical etchant is 50mg-100mg:100mL.

3. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The concentration of the chemical etchant is 0.05 mol / L to 0.3 mol / L.

4. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The chemical etchant is an acid or a base; When the chemical etchant is an acid, the hydrogen ions in the acid react with the oxygen atoms of Bi2WO6 in the Bi@Bi2WO6 material, causing the oxygen atoms of Bi2WO6 to be separated from the lattice, thereby forming oxygen vacancy defects; When the chemical etchant is an alkali, the hydroxide ions in the alkali react with the Bi or W atoms on the surface of the Bi@Bi2WO6 material to promote partial recombination of the crystal structure of the Bi@Bi2WO6 material and form oxygen vacancy defects.

5. The method for preparing the photocatalytic degradation composite material according to claim 4, characterized in that: The acid is one of hydrochloric acid, nitric acid and phosphoric acid; the alkali is one of sodium hydroxide, potassium hydroxide and ammonium hydroxide.

6. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The molar ratio of the bismuth salt, tungstate and reducing agent is 1-2:0.5-1:0.27-0.

55.

7. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 220° C. to 280° C., and the time of the solvent thermal reaction is 12 h to 24 h.

8. The method for preparing the photocatalytic degradation composite material according to claim 1, characterized in that: The reducing agent is hexadecyltrimethylammonium bromide.

9. A photocatalytic degradation composite material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the photocatalytic degradation composite material according to claim 9 in photocatalytic degradation of 2,4-dichlorophenol.

Citation Information

Patent Citations

  • Preparation method and photocatalytic performance of Bi2WO6-x micro-nano material

    CN106390992A

  • Method for selectively etching ferroelectric-based photocatalytic material to directionally construct heterostructure

    CN107790194A

  • Preparation method and application of tungsten oxide@bismuth tungstate heterojunction piezoelectric catalytic material

    CN113908827A

  • Method for enhancing polarity of bismuth tungstate nanosheet and application

    CN115350700A

  • Piezoelectric photocatalytic material with three-function heterostructure as well as preparation method and application of piezoelectric photocatalytic material

    CN116713022A